2017
DOI: 10.1111/jvim.14888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of 2 On‐Farm Tests for Estimating Somatic Cell Count in Quarter Milk Samples from Lactating Dairy Cattle

Abstract: BackgroundThe somatic cell count (SCC) is commonly used to monitor udder health and diagnose subclinical intramammary infection (IMI) in dairy cattle.HypothesisThe Somaticell test (ST)2 and California mastitis test (CMT) are clinically useful cow‐side tests for diagnosing subclinical IMI.AnimalsOne hundred and eleven dairy cows at dry‐off and 92 cows within 4–7 days postcalving.MethodsQuarter foremilk samples were obtained and analyzed with a DeLaval cell counter (DCC, reference method),1 ST, and CMT. The ST w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The study reported here was part of a series of studies investigating the diagnosis of SCM and IMI in lactating dairy cattle. Additional results have been published elsewhere (Kandeel et al, 2017(Kandeel et al, , 2018b.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…The study reported here was part of a series of studies investigating the diagnosis of SCM and IMI in lactating dairy cattle. Additional results have been published elsewhere (Kandeel et al, 2017(Kandeel et al, , 2018b.…”
Section: Methodsmentioning
confidence: 88%
“…Finally, a CMT result of ≥trace had Se of 0.52 and Sp of 0.71 in early-lactation quarters and Se of 0.63 and Sp of 0.53 in late-lactation quarters (Godden et al, 2017). Because of the imperfect test Se and Sp of SCC and the CMT for diagnosing SCM and IMI, as well as the subjective nature of the CMT, there remains a need for new on-farm tests that provide a rapid, practical, inexpensive, and accurate method for diagnosing quarters with SCM and IMI to guide selective intramammary treatment at dry-off and freshening (Godden et al, 2017;Kandeel et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…2009; Kandeel et al. 2018a). Similarly, Somaticell ® has been found comparable to microscopic SCC and CMT (Ferronatto et al.…”
Section: Diagnostics Through Technological Interventionsmentioning
confidence: 99%
“…These markers are detected by various diagnostic methods, ranging from conventional observations, SCC, California mastitis test (CMT) (Kandeel et al. 2018a, 2018b; Rossi et al. 2018) to advanced polymerase chain reaction (PCR) (Mahmmod 2013), loop-mediated isothermal amplification (LAMP) (Bosward et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation